Optimization of Electrochemical Phosphate Recovery from Industrial Sludge Residue Generated from Supercritical Water Oxidation Treatment with H2O2 (vol 13, pg 10141, 2018) - Tekbas, M.; Bektas, N. (Esg, 2019)
[No abstract available]